World War I and the origins of U.S. military intelligence - Gilbert, James L. (James Leslie) 1943- (Rowman & Littlefield, 2015)
World War I and the Origins of U.S. Military Intelligence provides the most authoritative overview of the birth of the army's modern use of intelligence services processes, starting with World War I. Following the natural division of the intelligence war, which was fought on both the home front and overseas, Gilbert tracks the development and use of army intelligence through the eyes of its principle architects: General Dennis B. Nolan and Colonel Ralph Deman. This book will not only appeal to students and scholars of military history and World War I, but it will also appeal to any reader interested in how modern intelligence operations came into being.